Effect of creep on time-dependent behaviour of prestressed concrete integral abutment bridge - Muhammad, Akilu (2014)
A parametric study was conducted to assess effect of creep on long term behaviour of prestressed concrete Integral Abutment Bridge (IAB). Varying backfill soil types were provided behind the bridge abutment and the interaction was modelled using linear springs. The effect of backfill soil type on the behaviour of the bridge was assessed through 75-year time-history simulations carried out in Commercial Finite Element Software (LUSAS). CEB-FIP 1990 creep model was used to analyse the linear viscoelastic behaviour of creep. The result has shown that creep and backfill soil type have a no severe effect on the behaviour of the bridge.